Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Tahun (2017-2021) - Hidayati, Habibatul; Asnathur Aisya, Perwira; Elva Dona; Romi Susanto; Yosep Eka Putra (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The purpose of this study is to determine the effect of profitability and leverage on firm value in the company's infrastructure. The variables in this study are Profitability and Leverage. Sampling using purposive sampling technique with certain criteria. The sample in this study are 16 infrastructure companies listed on the Indonesia Stock Exchange in 2017-2021. The analysis in this study uses panel regression analysis with the results showing that Leverage (DER) has no effect on firm value, while Profitability (ROA) has an effect on firm value.